"The Tongue Can Paint What the Eyes Cannot See": The Voice Actor and World-Building in Videogames. Issue 1 (2nd January 2022) - Southwick, Henry
ABSTRACT: The modern videogame industry is a massive economic and social engine. Much like the creation of a film, making a videogame requires a highly coordinated team of moving parts, with significant front-end costs. As such, to move units, all the artistic components need to be perfect to create a compelling world that demands continued engagement and brand loyalty. This article elucidates the specific essential role of the voice actor in the world building process, outlines how the voice is central to the immersive gaming experience, and critically assess the vocal tools used by practicing professionals for some of the leading games of the last decade.